Co-administration of curcumin and polyamines in high-fat diet induced obese rats: Assessment of changes in serum polyamine levels and some tissue parameters - Dumlu Bilgin, Gözde; Büyükuslu, Nihal; Eyüpoğlu, Ozan Emre (Elsevier Inc., 2023)
Obesity is a non-communicable chronic disease that continues to increase around the world. Recently, it has been shown that curcumin positively affects lipid, energy metabolism, and body weight change. Moreover, polyamines are aliphatic polycations, which can be found in all mammalian cells and foods and have been shown to prevent obesity through many different mechanisms. However, whether the co-administration of curcumin and polyamines has synergistic effects has yet to be clarified. Our study aimed to examine the effects of curcumin and polyamines on obesity and to assess the changes in serum polyamine levels and tissue parameters. 28 Sprague-Dawley male rats were fed a high-fat diet for 10 weeks to develop obesity, and then they were randomly divided into 4 groups as the control group (CONT), curcumin group (CUR), polyamine group (POL), curcumin and polyamine group (CUR+POL) and supplements were administered for 6 weeks. As a result, the lowest feed consumption in rats was recorded in the CUR+POL group, and the group with the lowest weight after supplements was the POL group, then the CUR+POL, CONT, and CUR groups, respectively. N-acetyl putrescine and GABA levels increased significantly after obesity development. The total histopathological score in fat, liver, and kidney tissues increased significantly in the CONT group. In the CUR+POL group, damage to the tissues was in the direction of recovery compared to the other groups, and the expression of NF-?B was significantly low. These results suggest that combined curcumin and polyamines may have protective effects.
Keywords: Curcumin; High-Fat Diet; Obesity; Polyamines